2019
DOI: 10.1515/ijnes-2018-0045
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Simulation Debriefings on Student Nurses’ Perceptions of Clinical Reasoning and Learning Transfer: A Mixed Methods Study

Abstract: To aim of this study was to explore undergraduate nursing student (n = 256) perceptions of clinical reasoning ability and learning transfer after participating in either a standard post simulation debriefing or a debriefing based on transfer of learning principles. Background: It is assumed that students will transfer what they have learned from simulation to real world practice, however, some students are unable to identify the relevance of simulated learning experiences if scenarios are dissimilar to clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The findings of the pilot study also underline practicalities for the use of clinical reasoning within a nursing program. The development of clinical decision making capability in nursing students is paramount to ensure quality and safe patient care (Bucknall et al, 2016;Forbes, Bucknall, & Hutchinson, 2016;Johnston, Nash, & Coyer, 2019). It is vital that students are supported and encouraged to develop higher level cognitive skills (Theobald, Windsor, & Forster, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the pilot study also underline practicalities for the use of clinical reasoning within a nursing program. The development of clinical decision making capability in nursing students is paramount to ensure quality and safe patient care (Bucknall et al, 2016;Forbes, Bucknall, & Hutchinson, 2016;Johnston, Nash, & Coyer, 2019). It is vital that students are supported and encouraged to develop higher level cognitive skills (Theobald, Windsor, & Forster, 2018).…”
Section: Discussionmentioning
confidence: 99%
“… 24 On the other hand, the teacher can promptly correct possible omissions, deficiencies and even errors in the practice. 25 Promoting the learning and application of knowledge by nursing students through personal experience and personal experience is the original intention and goal of teaching design based on CBT methods. 26 , 27 CBT is conducive to the reserve and enhancement of medical nursing knowledge for nursing students, and is conducive to flexibility and application when they are exposed to similar situations again.…”
Section: Discussionmentioning
confidence: 99%
“…Forbes found that critical thinking skills are transferrable when learning in a different discipline, but require explicit guidance from educators. In nursing, the effectiveness of simulation and debriefing experiences and the influence of tabletop exercises for disaster preparedness have been reported in relation to the transfer of learning.…”
Section: Literature Reviewmentioning
confidence: 99%